Qalbun Salim dalam Al-Qur’an Analisis Penafsiran Sayyid Quthb terhadap Q.S. As-Syu’ara Ayat 89 dalam Tafsir fi Zhilal Al-Qu’ran - Kurniawan, Rizki Rahmadiansyah (ANWARUL, 2023)
This study examines qolbun salim in the Qur'an and analyzes Sayyid Quth's interpretation of the Koran surah As-Syu'ara verse 89 in the fi zhilal interpretation of the Qur'an. Researchers use this type of research. Researchers use the type of library research (Library Research). The results of this study indicate that Sayyid Qutb in his commentary explained several things related to Qalbun in accordance with Q.S. As-Syu'aro, as follows: If a person's heart is silent from the awareness that Allah Almighty controls His servants, then he will be affected by feelings of arrogance and pride with the advantages he has. Such as wealth, power, strength or beauty. But if he remembers all the favors given by Allah subhanahu wa ta'ala, then he will humble himself because he feels that what he has is not his but a deposit from Allah subhanahu wa ta'ala. Strongly emphasizes the importance of sincere and sincere belief in worshiping Allah Subhanahu Wa Ta'ala. He is of the opinion that a clean and sincere heart is the main prerequisite in obtaining the pleasure of Allah subhanahu wa ta'ala and receiving His guidance. Therefore a clean heart is free from all forms of shirk. Sincerity in worship is not just an outward act, but includes an inner dimension. He emphasized that sincere and sincere worship must come from within the pure, with the sole intention of gaining the pleasure of Allah. Therefore Sayyid Qutb's view on Q.S As-Syu'aro, reminds Muslims to maintain purity of heart in worship. He is of the opinion that worship performed with a clean and sincere heart will bring blessings.